Study of a wide-aperture combined deformable mirror for high-power pulsed phosphate glass lasers. (December 2015) - Samarkin, V.V.; Aleksandrov, A.G.; Jitsuno, T.; Romanov, P.N.; Rukosuev, A.L.; Kudryashov, A.V.
Abstract: A deformable mirror with the size of controlled by bimorph piezoceramic plates and multilayer piezo stacks is developed. The response functions of individual actuators and the measurements of the flatness of the deformable mirror surface are presented. The study of mirrors with an interferometer and a wavefront sensor has shown that it is possible to improve the surface flatness down to a residual roughness of (RMS). The possibility of correction of beam aberrations in an ultra-high-power laser using the created bimorph mirror is demonstrated.